2014
DOI: 10.1038/gt.2014.48
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional duration of immune responses to HCV NS3/4A induced by DNA vaccination

Abstract: We have investigated the ability of hepatitis C virus non-structural (NS) 3/4A-DNA-based vaccines to activate long-term cell-mediated immune responses in mice. Wild-type and synthetic codon optimized (co) NS3/4A DNA vaccines have previously been shown to be immunogenic in mice, rabbits and humans, although we have very poor knowledge about the longevity of the immune responses primed. We therefore analyzed the functionality of primed NS3/4A-specific immune responses in BALB/c (H-2d) and/or C57BL/6J (H-2b) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Guan et al showed that adenovector expressing truncated NS3 and core not only stimulate humoral immune response but also initiate strong cellular immunity against specific antigen; in addition, it provides a reasonable protective response . The current study revealed significant immune inducible effect and significant tumor growth inhibition of NS3 in mice model compared to control groups that may be due to immunodominat epitope in NS3 …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Guan et al showed that adenovector expressing truncated NS3 and core not only stimulate humoral immune response but also initiate strong cellular immunity against specific antigen; in addition, it provides a reasonable protective response . The current study revealed significant immune inducible effect and significant tumor growth inhibition of NS3 in mice model compared to control groups that may be due to immunodominat epitope in NS3 …”
Section: Discussionmentioning
confidence: 61%
“…34 The current study revealed significant immune inducible effect and significant tumor growth inhibition of NS3 in mice model compared to control groups that may be due to immunodominat epitope in NS3. 27,35,36 LLO contains four structural domains and all of these domains induce apoptosis through caspase dependent and independent mechanisms. 37 Because of its toxicity, it cannot be used thoroughly as an applicable adjuvant, and it is necessary to remove toxic domains.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, strategies for developing a therapeutic vaccine against HCV infection have focused on inducing T-cell responses to NS antigens [6,10,11,22,25,[33][34][35][36][37][38]. Ad vectors are also being employed in a phase I vaccine trial to deliver NS HCV proteins (NS3-5B) to 36 healthy Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Production of IFN-γ and IL-2 cytokines was determined by a commercially available ELISpot assay (Mabtech, Nacka Strand, Sweden) as described previously. 23 The number of spots was counted using the AID iSpot reader and software version 7.0 (AID, Strassberg, Germany). The number of spots (cytokine-producing cells) was determined at each concentration of peptide or protein, and the results given as the number of IFN-γ or IL-2-producing cells per 10 6 cells.…”
Section: Methodsmentioning
confidence: 99%